Exploration of Oxetanes and Azetidines in Structure-Based Drug Design - Ramisetty, Mohana Krishna; Yadav, Vikas; Venkitasamy, Kesavan; Baskaran, Sundarababu (Synlett, 2025)
Oxetane and azetidine motifs are widely used in medicinal chemistry to enhance various attributes such as hydrophilicity, metabolic stability, hydrophobicity, and conformational preference. These stable structures are present in numerous bioactive compounds, including FDA-validated therapeutic agents. This study aims to demonstrate the use of oxetane and azetidine ring systems as bioisosteric replacements for isopropyl groups in the development of novel lead candidates. The objective is to improve physicochemical and structural characteristics to facilitate effective molecular optimization, improve pharmacological activity, and simplify synthetic pathways. This can ultimately increase the chances of discovering medication that is more efficient and safer to use. We report the virtual screening of selected 14 approved drugs with a replacement of isopropyl to oxetane and azetidine group transformation, enabling optimization for receptor binding potential and absorption, distribution, metabolism, and excretion (ADME) properties. The results indicate that oxetane alectinib (−6.906 kcal/mol), azetidine procarbazine (−8.083 kcal/mol), azetidine erdafitinib (−7.677 kcal/mol), oxetane anastrozole (−7.454 kcal/mol), azetidine nateglinide (−6.686 kcal/mol), oxetane repaglinide (−7.831 kcal/mol), oxetane nilutamide (−9.649 kcal/mol), and oxetane proguanil (−8.555 kcal/mol) have excellent molecular affinity when compared to their parent molecule. This perspective aims to inspire medicinal chemists to explore the use of oxetane and azetidine moieties in the development of effective drug candidates.
Keywords: Oxetane; Azetidine; Isopropyl group; Drugs; Binding potential; ADME properties